On the Issue of Abuse of Labour Rights (Scientificpractical interpretations of Labour Code of RA) - Petrosyan, G. (Bulletin of Yerevan University C: Jurisprudence, 2017)
Domestic jurisprudence doesn’t provide theoretical conclusions and interpretations on one of the important principles of Labour Code of RA-the principle of prohibition of labour rights` abuse, which is causing considerable risk to proper application of that clause of law. In fact, there is a situation, when the law prohibits the abuse of right without interpreting it. This leads to entailing the clause of law into individual solutions by law implementing and law enforcement entities. The aim of this article is to clarify the essence of phrase of ‘‘abuse of employment rights’’, the attributes of abuse of right, as well as to emphasize the peculiarities, that allow to differentiate abuse of employment rights from exercising rights in good faith and from ordinary labour offences. In order to solve these problems the sources of contemporary Russian labour law literature have been scrutinized, comparative analysis has been carried out on general and special norms of Labour Code of RA and it has been attempted to emphasize the borders of exercising and abusing of employment rights using particular examples.